La recherche en sciences humaines et sociales sur l’objet pesticide dans le cadre académique français : état des lieux et perspectives - Eve Bureau-Point; Ludovic Temple (VertigO)
This article proposes an analytical review of the research in the Humanities and Social sciences (HSS) on pesticides carried out in the French academic context since 1945. The research is presented from a historical perspective that takes into account the agricultural, political, macroeconomic, and institutional context in which it was published. The authors distinguish two main phases: a first (1945-2000) where pesticides are mainly understood as a resource for agricultural modernization, and a second (2000-2021) where they emerged gradually as a field of study in the Humanities and Social sciences, in which they are considered as a more controversial object. This analytical review highlights the community of researchers involved in the subject in France and abroad, and the main themes explored during this period.